Car rental management sytem with SMS alert - Fazreeny, Adnan (2013)
Technology is an absolute need we cannot escape from. It has an important role in most aspects of our lives. In other words, it is solution of every mankind problems. The importance of technology is aiming for comfort of use in whichever form it is. In this paper, it discuss about changing convenient method in managing car rental to standalone system. Before this, commonly car rental manages by record manually in a paper. These methods are not systematic and time consuming during searching and updating data. Other than that, when record data in file will risk of losing information as burnt in fire, ink split and so on. By proposed Car Rental Management System with SMS Alert will promotes better management in future. In this system, user can log on into the system and key in detail and wait for the admin response with rent a car status. There are several functions such as record information, update car status, and deleting data. In addition, it consist of special function where customer will receive SMS reminder to return a car on time and customer should not worried if forget password because SMS alert function able to sent recovery password to user. As a result, this system will make sure overall management process done efficiently and reduce time and cost in future.